A versatile and safe mobility assistant. - Lankenau, A. (IEEE Robotics and automation magazine)
The Bremen autonomous wheelchair implements obstacle avoidance plus driving and routing assistance in a shared-control system. This article shows how the tasks of reliably detecting obstacles in the environment and safely avoiding these obstructions are solved